Pengaruh Perencanaan Produksi dan Efesiensi Operasional Terhadap Kinerja Operasional pada PT. Kamaltek Indonesia - Mutia Ayu; Ardiansyah, Riva; WIJAYA, PERDI ARIF (Metode : Jurnal Teknik Industri, 2025)
The purpose of this study is to evaluate how production planning and operational efficiency impact the operational performance of PT Kamaltek Indonesia. In the textile industry, careful production planning and efficient use of resources are considered important for improving company productivity and competitiveness. This study uses a quantitative approach employing descriptive and causal methods. Primary data was collected through a questionnaire administered to 96 employees working in the production and operational divisions. Validity, reliability, and hypothesis tests (F-test and t-test) were used to analyze the data. The results of the study indicate that both production planning and operational efficiency positively and significantly influence operational performance. With the highest regression coefficient, operational efficiency has a greater impact than production planning. The coefficient of determination of 93.8% indicates that this model is highly effective in explaining variations in operational performance. This study emphasizes the importance of implementing lean manufacturing and technology integration to support company operations in the Industry 4.0 era.